What are the career implications of "seeing eye to eye"? Examining the role of leader–member exchange (LMX) agreement on employability and career outcomes. Issue 4 (17th November 2020) - Epitropaki, Olga; Marstand, Anders Friis; Van der Heijden, Beatrice; Bozionelos, Nikos; Mylonopoulos, Nikolaos; Van der Heijde, Claudia; Scholarios, Dora; Mikkelsen, Aslaug; Marzec, Izabela; Jędrzejowicz, Piotr; ,
Abstract: Are there career benefits to leaders and followers agreeing about the quality of their leader–member exchange (LMX) relationship? Is LMX disagreement always detrimental for a follower's career? Can the examination of LMX agreement as a substantive variable help us cast new light on some of the inconclusive findings of past research on LMX and career outcomes? These questions motivate our research. Using theories of social exchange and sponsorship, and responses from 967 leader–follower dyads of Information and Communication Technology (ICT) professionals in seven European countries, we examined the role of LMX agreement on subjective and objective career outcomes. After conducting polynomial regression combined with response surface analysis, we found that both follower‐rated and leader‐rated employability were higher when the leader agreed with the follower at a high level of LMX (vs. a low level of LMX). In case of disagreement, strong support was found for leader‐rated employability being higher when the leader's perceptions of LMX exceeded those of their follower. Furthermore, follower‐rated employability was found to mediate the relationship between LMX (dis)agreement and perceived career success, promotions, salary, and bonuses. Support was also found for the mediating role of leader‐rated employability in the case of perceived career success, promotions, and salary but not for bonuses. Our findings highlight the importance of LMX (dis)agreement for career outcomes and further point to the possibility of employability offering an alternative explanation for the mixed findings of past LMX–career research.